Effect of DU meridian acupuncture and temporal three-needle on vascular protection mechanisms in patients with acute cerebral infarction: a randomized controlled evaluator-blinded clinical trial - Sun, Yawen; Zhong, Qiqi; Hou, Yingci; Liu, Xin; Yan, Mingyue; Zhou, Luolin; Liu, Shiyi; Hong, Senkai; He, Jun (Frontiers in Neurology, 2025)
BackgroundThe incidence of acute ischemic stroke has been rising steadily in China and globally, with its high mortality and disability rates significantly affecting quality of life. As an important adjunct therapy, acupuncture has been widely implemented in stroke management. Emerging studies have investigated the effects of DU meridian and Chong Mai acupuncture on ischemic hemiparesis; however, the vascular protective mechanisms of electroacupuncture therapy targeting these meridians require further elucidation in stroke rehabilitation research.ObjectiveThis prospective cohort study aims to investigate the clinical efficacy and limitations of DU meridian acupuncture combined with Temporal Triple Needling (Sanjian) therapy in stroke rehabilitation. The intervention’s therapeutic potential is evaluated through its modulatory effects on CD14+/CD14- monocyte subpopulations within peripheral blood mononuclear cells (PBMCs), with particular focus on angiogenesis-mediated vascular protection mechanisms.MethodsSixty-six patients with acute ischemic stroke will be randomly assigned 1:1 to control (conventional basal therapy, n = 33) and acupuncture (conventional standard stroke care + acupuncture, n = 33) groups for 10 days of intervention. The primary outcome is NIHSS score. The secondary outcomes: BMI and mRS scores, the level of TNF-A and IL-1B in serum, vascular endothelial growth factor (VEGF), Endocan ES, CD14+ and CD14- levels of peripheral blood mononuclear cells.DiscussionThe aim of this study is to investigate whether electroacupuncture targeting the DU meridian combined with Temporal Triple Needling (Sanjian) improves cerebrovascular endothelial function in acute ischemic stroke patients, thereby reducing the NIHSS score and preventing further disease progression. This study also aims to contribute positively to the development of relevant clinical treatment protocols and to facilitate further research into the underlying mechanisms of these effects.Clinical trial registrationInternational Traditional Medicine Clinical Trial Registry ITMCTR2024000508.